Incidence of and risk factors for severe hypoglycaemia in treated type 2 diabetes mellitus patients in the UK – a nested case–control analysis. Issue 9 (19th March 2014) - Bruderer, S. G.; Bodmer, M.; Jick, S. S.; Bader, G.; Schlienger, R. G.; Meier, C. R.
<x xml:space="preserve">Abstract</x> Aims To assess incidence rates (IRs) of and identify risk factors for incident severe hypoglycaemia in patients with type 2 diabetes newly treated with antidiabetic drugs. Methods Using the UK‐based General Practice Research Database, we performed a retrospective cohort study between 1994 and 2011 and a nested case–control analysis. Ten controls from the population at risk were matched to each case with a recorded severe hypoglycaemia during follow‐up on general practice, years of history in the database and calendar time. Using multivariate conditional logistic regression analyses, we adjusted for potential confounders. Results Of 130 761 patients with newly treated type 2 diabetes (mean age 61.7 ± 13.0 years), 690 (0.5%) had an incident episode of severe hypoglycaemia recorded [estimated IR 11.97 (95% confidence interval, CI, 11.11–12.90) per 10 000 person‐years (PYs)]. The IR was markedly higher in insulin users [49.64 (95% CI, 44.08–55.89) per 10 000 PYs] than in patients not using insulin [8.03 (95% CI, 7.30–8.84) per 10 000 PYs]. Based on results of the nested case–control analysis increasing age [≥75 vs. 20–59 years; adjusted odds ratio (OR), 2.27; 95% CI, 1.65–3.12], cognitive impairment/dementia (adjusted OR, 2.00; 95% CI, 1.37–2.91), renal failure (adjusted OR, 1.34; 95% CI, 1.04–1.71), current use of sulphonylureas (adjusted OR, 4.45; 95% CI, 3.53–5.60) and current insulin use (adjusted OR, 11.83; 95% CI, 9.00–15.54) were all associated with an increased risk of severe hypoglycaemia. Conclusions Severe hypoglycaemia was recorded in 12 cases per 10 000 PYs. Risk factors for severe hypoglycaemia included increasing age, renal failure, cognitive impairment/dementia, and current use of insulin or sulphonylureas.